Evolution the whole story - Parker, Steve (Thames & Hudson Ltd., 2015)
Evolution: The Whole Story provides an in-depth account of evolution, one of the ultimate keystone theories in modern science. Ten experts survey how each of Earth's major groups of living things diversified and evolved through time. Using visual features that make the story comprehensible, the book gives readers, even those with no previous knowledge of the topic, a clear understanding of evolution and how it brought us to the present day.